The Aspect Hypothesis and L2 Russian - Whitehead Martelle, Wendy; Shirai, Yasuhiro (Frontiers in Language Sciences, 2023)
Numerous studies have been conducted regarding the second language acquisition of tense-aspect morphology. A prevailing principle in this area is the Aspect Hypothesis, which predicts that learners are influenced by lexical aspect when applying tense-aspect markers (specifically, that learners will associate perfective/past markers with telic verbs and imperfective/past markers with atelic verbs). The Aspect Hypothesis has been widely tested in the acquisition of English, several Romance languages, Japanese, and Chinese. However, few studies have explored the second language acquisition of aspect in Slavic languages, which tend to have morphologically rich and complex tense-aspect systems. Additionally, few studies address the potential impact of modality and activity (for example, written vs. oral output) on the production of aspect. The present study addresses these gaps by investigating how second language learners of Russian at varying proficiency levels use aspectual markers in the past tense when producing oral and written narratives. Data from written narratives (N=42) and oral narratives (N=42) were analyzed for lexical aspect and tense-aspect marking. The results indicate that the Aspect Hypothesis is supported to varying degrees depending on the activity: the activity involving lower planning levels (oral narratives) was more supportive of the Aspect Hypothesis, compared to the written narrative task, which involves a higher level of planning. However, the results also show that the aspectual production of beginning-level Russian learners is not consistent with certain predictions of the Aspect Hypothesis. The study concludes by discussing the role of instruction as a possible explanation for this inconsistency.